PENGARUH MODEL PEMBELAJARAN COMPLETE SENTENCE BERBANTUAN MEDIA LITERASI DIGITAL TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V GUGUS V KECAMATAN BUSUNGBIU KABUPATEN BULELENG (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This research was conducted to determine the effect of the Complete Sentence Learning Model Assisted by Digital Literacy Media on the Indonesian Language learning outcomes of Class V Students in Group V, Busungbiu District, Buleleng Regency. This research is motivated by the fact that students' learning outcomes are low in Indonesian subjects in Class V Cluster V, Busungbiu District, Buleleng Regency. The low learning outcomes of Indonesian can be seen that students feel bored and bored with the teacher's method of explaining to students, as a result, students prefer to sort out rumpi and play with their friends at a bench rather than observing the teacher who is explaining the material. This research uses qualitative experimental research, in this research 121 class V students of Cluster V, Busungbiu District, Buleleng Regency are used as the population. Class V of SDN 3 Pucaksari totaling 19 students was used as the experimental class, and class V of SDN 2 Bongancina as many as 20 students was used as the control class. The results were obtained from the determination of the sample through simple random sampling. Based on the average value of the Indonesian language learning outcomes of the experimental class students was 75.89, while the average Indonesian language learning outcomes of the control class students was 68.1. With the results of the T-test where ttable with a significance level of 5% and db 37 is 2.027, compared to the results of tcount is 7.086, so it can be stated that 7.086 > 2.027. Thus, the form of Complete Sentence learning assisted by Digital Literacy media has a significant effect on the learning outcomes of Indonesian students in class V Group V, Busungbiu District, Buleleng Regency.